Non-pulmonary lesions associated with a demonecrotic toxin-producing Pasteurella multocida D:3 infection in rabbits - Zamri Saad M. (2021)
Six New Zealand White rabbits inoculated intranasally with Pasteurella multocida D: 3 died acutely as early as day 3 post-infection and developed lesions in the liver, kidney, heart and brain apart from the nasal cavity, trachea and lungs. Pasteurella multocida D: 3 was isolated from these organs. All affected organs were severely congested. There were diffused hepatocyte degeneration with cytoplasmic vacuolation, particularly those around the portal triad and central veins. The hepatocyte enlargements resulted in narrowing of the sinusoids. Several Kupffer cells that lined the affected sinusoids appeared enlarged. The heart was haemorrhagic and the myocardial fibres were necrotic, atrophied and separated by oedema. Heterophils and mononuclear cells infiltrated the myocardium. The pericardium was thickened with fibrin deposition and heterophil infiltration. Suppurative meningoencephalitis and axonal demyelination were observed in two rabbits that died at day 4 post-infection. Rabbits that survived until day 21 post-infection did not develop the non-pulmonary lesions and had no P. multocida in the non-pulmonary sites.